Supply chain finance: Historical foundations, current research, future developments. Issue 2 (March 2019) - Caniato, Federico; Henke, Michael; Zsidisin, George A.
Abstract: It is widely agreed that supply chains encompass and integrate material, information, and financial flows across organizations. There is a robust history and continually expanding research agenda investigating supply chain management practice and theory associated with material and information flows and processes. However, the management of financial flows from a supply chain perspective and in combination with the other flows, usually referred to as supply chain finance (SCF), has been under-investigated. Our understanding of SCF approaches and solutions in purchasing and supply management (PSM) is only starting to form. The purpose of this editorial is to provide some grounding of initial studies and concepts of SCF, illustrate new and emerging thought in this discourse with articles published in this special issue, and speculate how the SCF domain may evolve in theory and practice with the advent of new digital technologies and big data analytics. Highlights: Provides a summary of initial studies and concepts in supply chain finance. Offers insight as to how the SCF domain may evolve in theory and practice with the advent of new digital technologies and big data analytics.